Evaluation of the Role of Ethylene Vinyl Acetate on the Thermo-Mechanical Properties of PET/HDPE Blends - Hellati, A.; Boufassa, S. (Engineering, Technology & Applied Science Research, 2022)
In this paper, blends of recycled polyethylene terephthalate (r-PET) and high-density polyethylene (HDPE) with and without a compatibilizer were prepared using a Brabender Haake Rheocord at 270°C and 32rpm. Ethylene vinyl acetate was chosen as the compatibilizer and its proportion was set to 5, 7, and 10 wt%. The thermal properties and crystallization behavior were determined by Differential Scanning Calorimetry (DSC). Micromechanical properties were also investigated using a Vickers microindentation tester. The DSC analysis indicates that the melting temperature of r-PET and HDPE in all the blends, compatibilized and uncompatibilized, remains constant and almost the same as those of the pure component. On the other hand, it is shown that the degree of crystallinity of HDPE in the blends calculated by DSC depends on the composition of the polymeric mixture. However, the Hardness (H) decreases with increasing r-PET content until 50/50 composition of r-PET/HDPE is reached, whereas for larger r-PET content values, H increases. The same trend was obtained with the addition of the compatibilizer.